A long-acting, dual-agonist analogue of lamprey GLP-1 shows potent insulinotropic, β-cell protective, and anorexic activities and improves glucose homeostasis in high fat-fed mice. (1st January 2020) - Graham, Galyna V.; McCloskey, Andrew; Abdel-Wahab, Yasser H.; Conlon, J. Michael; Flatt, Peter R.
Abstract: Peptidase-resistant analogues of GLP-1 peptides from sea lamprey and paddlefish ([D-Ala 2 ]palmitoyl-lamprey GLP-1 and [D-Ala 2 ]palmitoyl-paddlefish GLP-1) produced significant (P ≤ 0.05) and concentration-dependent increases in insulin release from BRIN-BD11 clonal β-cells and from isolated mouse islets. Both analogues retained the ability of the native peptides to activate both the GLP-1 receptor (GLP1R) and the glucagon receptor (GCGR). [D-Ala 2 ]palmitoyl-lamprey GLP-1 significantly (P < 0.001) stimulated proliferation of BRIN-BD11 cells and protected against cytokine-induced apoptosis. Administration of the lamprey analogue (25 nmol/kg body weight) to lean mice up to 4 h before a glucose load improved glucose tolerance and increased plasma insulin concentrations. Twice daily administration of the lamprey GLP-1 analogue to high fat-fed mice for 21 days decreased body weight, food intake, and circulating glucose and insulin concentrations. The analogue significantly improved glucose tolerance and insulin sensitivity with beneficial effects on islet β-cell area and insulin secretory responsiveness. Islet gene expression of Glp1r, Gcgr and Gipr significantly increased. The lamprey GLP-1 analogue shows therapeutic promise for treatment of patients with obesity-related Type 2 diabetes. Highlights: Lamprey GLP-1 (l-GLP-1) analogue is resistant to degradation by plasma peptidases. l-GLP-1 stimulated insulin release from BRIN-BD11 clonal β-cells and mouse islets. l-GLP-1 stimulated proliferation of BRIN-BD11 cells and protected against apoptosis. l-GLP-1 inhibited food intake and improved glucose tolerance in lean mice. l-GLP-1 displayed diverse anti-diabetic properties in high fat-fed mice.